Relative accuracy of social and medical determinants of suicide in electronic health records. (2nd September 2020) - Alemi, Farrokh; Avramovic, Sanja; Renshaw, Keith D.; Kanchi, Rania; Schwartz, Mark
Abstract: Objective: This paper compares the accuracy of predicting suicide from Social Determinants of Health (SDoH) or history of illness. Population Studied: 5 313 965 Veterans who at least had two primary care visits between 2008 and 2016. Study Design: The dependent variable was suicide or intentional self‐injury. The independent variables were 10 495 International Classification of Disease (ICD) Version 9 codes, age, and gender. The ICD codes included 40 V‐codes used for measuring SDoH, such as family disruption, family history of substance abuse, lack of education, legal impediments, social isolation, unemployment, and homelessness. The sample was randomly divided into training (90 percent) and validation (10 percent) sets. Area under the receiver operating characteristic (AROC) was used to measure accuracy of predictions in the validation set. Principal Findings: Separate analyses were done for inpatient and outpatient codes; the results were similar. In the hospitalized group, the mean age was 67.2 years, and 92.1 percent were male. The mean number of medical diagnostic codes during the study period was 37; and 12.9 percent had at least one SDoH V‐code. At least one episode of suicide or intentional self‐injury occurred in 1.89 percent of cases. SDoH V‐codes, on average, elevated the risk of suicide or intentional self‐injury by 24‐fold (ranging from 4‐ to 86‐fold). An index of 40 SDoH codes predicted suicide or intentional self‐injury with an AROC of 0.64. An index of 10 445 medical diagnoses, without SDoH V‐codes, had AROC of 0.77. The combined SDoH and medical diagnoses codes also had AROC of 0.77. Conclusion: In predicting suicide or intentional self‐harm, SDoH V‐codes add negligible information beyond what is already available in medical diagnosis codes. Implications for Practice: Policies that affect SDoH (eg, housing policies, resilience training) may not have an impact on suicide rates, if they do not change the underlying medical causes of SDoH.